Analysis of Metoxyl and Galacturonate Contents from Pectin of Banana Peel Waste Combined with Sappan Wood - Asfar, Andi Muhamad Iqbal Akbar; Mukhsen, Muh Iqbal; Asfar, Andi Muhammad Irfan Taufan; Budianto, Eko; Damayanti, Jeanne Dewi (Jurnal Bahan Alam Terbarukan, 2024)
The production of banana plants (Musaceaea sp.) ranks first in agricultural output in Indonesia, but this is not balanced by the processing of waste from banana peels, which is a large amount. Therefore, an attempt is made to use banana peel waste as raw material for making pectin. Pectin is used as a functional component in the food industry because of its ability to form thin gels and stabilize proteins. Pectin is also used as a filler in the paper and textile industries, and as a thickener in the rubber industry. This research aims to determine the effect of extraction time and temperature on the quality of pectin from Kepok banana peels. The method used is extraction through Ultrasonic Assisted Solvent Extraction (UASE) in 40 kHz. Banana peels that had been dried and ground into powder were extracted with 0.1 N HCl at temperatures of 70 oC, 80 oC and 90 oC. The variables used in this extraction are variations in extraction time, namely 60 minutes and 80 minutes. The extracted solution is filtered and thickened to half the volume of the original filtrate by heating, then the pectin is thickened using acid ethanol. The pectin precipitate was washed using 96% alcohol until it was free of chloride and the precipitate was separated using a vacuum and then dried in an oven then to analysis of pectin using methoxyl and galacturonate as method to determine pectin quality form banana peel waste. The research results showed that the pectin quality was optimum at a temperature of 90 oC for 80 minutes with a methoxyl content of 4.12% (low methoxyl) and a galacturonic acid content of 79.96%.